2023
DOI: 10.3390/life13091808
|View full text |Cite
|
Sign up to set email alerts
|

Novel Diagnostic and Therapeutic Approaches to Temporomandibular Dysfunction: A Narrative Review

Brendan Moxley,
William Stevens,
Joel Sneed
et al.

Abstract: Temporomandibular dysfunction (TMD) is a burgeoning area of study within the dental field. TMD is caused by abnormalities in the temporomandibular joint or muscles of mastication and can lead to pain, loss of function, and other complications. As this area of patient care receives increased focus, the ability to accurately diagnose TMD becomes paramount. The aim of this review is to summarize novel diagnostic and therapeutic techniques that have been proposed within the last approximately 3 years in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…ChatGPT-4 as auxiliary tool in the temporomandibular disorders diagnostic: An opinion Dear editor, Temporomandibular disorders (TMD) are a complex clinical condition characterized by the presence of musculoskeletal abnormalities, such as dysfunctions in the temporomandibular joint or masticatory muscles. 1 The most commonly reported symptoms include headaches, loss of function, neck pain and discomfort, all of which have a negative impact on the quality of life. 1,2 Currently, magnetic resonance imaging (MRI) and computed tomography (CT) are considered the gold standard of assessing these maxillofacial disorders.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
See 1 more Smart Citation
“…ChatGPT-4 as auxiliary tool in the temporomandibular disorders diagnostic: An opinion Dear editor, Temporomandibular disorders (TMD) are a complex clinical condition characterized by the presence of musculoskeletal abnormalities, such as dysfunctions in the temporomandibular joint or masticatory muscles. 1 The most commonly reported symptoms include headaches, loss of function, neck pain and discomfort, all of which have a negative impact on the quality of life. 1,2 Currently, magnetic resonance imaging (MRI) and computed tomography (CT) are considered the gold standard of assessing these maxillofacial disorders.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…1 The most commonly reported symptoms include headaches, loss of function, neck pain and discomfort, all of which have a negative impact on the quality of life. 1,2 Currently, magnetic resonance imaging (MRI) and computed tomography (CT) are considered the gold standard of assessing these maxillofacial disorders. However, failures in diagnostic interpretation can lead to delays in emergency care.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…In the dynamic and complex field of temporomandibular disorders (TMDs), keeping our knowledge up to date is of great importance. The following Special Issue focuses on novel as well as established therapies [1][2][3][4][5][6], with an additional glimpse at diagnostic improving tools and novel approaches [4,7,8], as well as epidemiological data [9].…”
mentioning
confidence: 99%
“…Many patients must visit several specialists, often from various fields, before finding help. Moxley et al, based on the recent literature, pointed to the possibility of introducing an artificial neural network-based program to aid the diagnostic process [4]. Kreiner et al, who created the program, showed its significant advantage over the diagnostic abilities of inexperienced general dental practitioners, as it has a sensitivity and specificity close to 100% [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation